2012
DOI: 10.3382/ps.2011-01813
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the relationship of mycotoxins with biochemical and hematological parameters in broilers

Abstract: A meta-analysis was carried out to study the association of mycotoxins with hematological and biochemical profiles in broilers. Ninety-eight articles published between 1980 and 2009 were used in the database, totaling 37,371 broilers. The information was selected from the Materials and Methods and Results sections in the selected articles and then tabulated in a database. Meta-analysis followed 3 sequential analyses: graphic, correlation, and variance-covariance. Mycotoxins reduced (P < 0.05) the hematocrit (-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 17 publications
5
26
0
3
Order By: Relevance
“…In this study, a high level of NH 3 decreased the serum globulin concentration on the third week, which is partly in agreement with the results of previous research (Javed et al, 1995;Stanley et al, 2004;Gao et al, 2009;Andretta et al, 2012;Li et al, 2012). Moreover, in this study, NH 3 and RH had an additive detrimental effect on albumin, total protein, and globulin.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a high level of NH 3 decreased the serum globulin concentration on the third week, which is partly in agreement with the results of previous research (Javed et al, 1995;Stanley et al, 2004;Gao et al, 2009;Andretta et al, 2012;Li et al, 2012). Moreover, in this study, NH 3 and RH had an additive detrimental effect on albumin, total protein, and globulin.…”
Section: Discussionsupporting
confidence: 93%
“…This small body of evidence (summarized in Supplemental Table 3) indicates that aflatoxin may cause low hematocrit and hemoglobin,66,67 low iron absorption,68 and microcytic hypochromic anemia,69 all of which are characteristic of iron deficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The findings of this study were in agreement with the results of Aravind et al [32] . In another study, 14% increase for AST and 17% increase for ALT serum levels were observed in chickens fed aflatoxin contaminated diets [33] . One of the symptoms for hyperplasmy is a significant increase in serum levels of ALT and GGT [34] .…”
Section: Discussionmentioning
confidence: 99%